Passive Window Energy Performance in Buildings: Modeling of Apartment Buildings in Indonesia - Laurentius Kevin Hendinata; Nur Abdillah Siddiq; Ahmad Ilham Rokhul Fikri; Michael Alfano Suprapto; Ribka Prilia (Universitas Atma Jaya Yogyakarta, 2023)
Along with urban growth in urban areas and energy consumption, which continues to increase every year, the selection of windows in the initial design is essential to obtain buildings that are not energy intensive. Selecting the correct window in the blueprint design reduces building energy consumption. Smart windows, especially thermochromic windows, are one of the most promising window technologies because they are the most economical and have passive control with zero energy input, which holds good promise for energy-saving applications. Apart from that, double-glazing windows are also frequently used in energy-saving applications. Therefore, a study compared the energy-saving potential of thermochromic and double-glazing windows to clear glass windows, using computer modeling through EnergyPlus, in high-rise apartment buildings in cities throughout Indonesia's diverse climates. From the modeling results, total energy consumption can be reduced by around 8.91% to 10.96% of total building energy consumption by replacing the conventional clear glass with double-glazing windows or more able to reduce about 20.22% to 24.19% by replacing the conventional clear glass with thermochromic windows. Furthermore, this potential varies depending on geometric shapes, materials, building facades, local climate, and building orientation. Nevertheless, considering the potential benefits, these windows are highly suitable for application in buildings seeking to reduce their energy consumption and improve energy efficiency.